A novel role for multifunctional NAC transcription factor SlNOR-like1: Enhancing flavonoid accumulation in tomato fruit exocarp by modulating glycosylation modification - Gangshuai Liu; Yueming Tang; Yiwen Yang; Jinghong Luo; Xiaodan Zhao; Daqi Fu; Jia Gao (Food Bioscience, 2026)

Abandoned farmland identification, reclamation potential assessment, and zonal management: A case study of Heshan City in China - Changsheng Xiong; Yueming Gao; Yumo Xing; Zhuo Xie; Tianxiao Zhou (Ecological Engineering, 2026)

Dynamic patterns of constraints, drivers and impacts of land-based aquaculture areas and their implications: A case of Guangdong, China from 1990 to 2020 - Ku Gao; Xiaomei Yang; Zhihua Wang; Yueming Liu; Feilin Lai; Junyao Zhang (Land Use Policy, 2026)

Waste eggshell-modified biochar for phosphorus recovery and its potential reuse as a sustainable fertilizer - Yixuan Feng; Yueming Chen; Xilin Guan; Zichao Zhao; Xinhao Gao; Xiaoning Liu; Shenzhong Tian (Journal of Environmental Chemical Engineering, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

Spatiotemporal heterogeneity of human footprint across China's coastal zone: Integrating geomorphic and policy drivers - Dan Meng; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Ku Gao (Ocean & Coastal Management, 2026)

Quantifying the spatiotemporal characteristics and driving mechanisms of greenhouse gas emissions from the wastewater treatment sectors in Chinese cities - Xiaona Wang; Yueming Gao; Nana Zhao (Environmental Research, 2026)

Mitigating methane emissions from municipal solid waste in Chinese cities - Yueming Gao; Yang Duan; Wei Zhang; Nana Zhao; Yuan Wang; Zhenyu Ding; Wenjun Wu; Dong Cao; Hongqiang Jiang (Journal of Environmental Management, 2026)

Physiological and Metabolomic Analysis in Roots of Hordeum jubatum L. In Response to Iso-osmotic Stress - Peilin Han; Xiaolin Di; Bing Gao; Jinji Han; Yueming Li; Xiaoxia Deng; Zhuoran Tan; Jingnan Zhang; Jinghong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

The effects of gradient magnetic field on the detailed flow behavior of diffusion flames: Application for stabilizing coal bed methane flames - Hetong Gao; Yueming Wang; Minmin Zhou; Lunbo Duan (Fuel, 2025)

The impact of land use on the composition of dissolved organic matter and its relationship with microbes in a river basin in Northwestern China: Insights into microbial community structure and metabolic function - Xiang Zhu; Xinhua Gao; Yueming Zhu; Jingjie Huang; Fuquan Peng; Qingqing Pang; Fei Yang; Lei Xie; Zulin Hua; Longmian Wang (Journal of Environmental Management, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Identification of novel natural anti-browning agents based on phenotypic and metabolites differences in potato cultivars - Yueming Tang; Yiwen Yang; Fangyao Luo; Jinghong Luo; Jianjun Hu; Haoqiang Yu; Wanchen Li; Jia Gao; Fengling Fu (Food Chemistry, 2025)

An update of aurones: food resource, health benefit, biosynthesis and application - Jiali Yang; Zhengjiao Gao; Zhiqian Yu; Yu Hou; Dingtao Tang; Huiling Yan; Fuwang Wu; Sui Kiat Chang; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Spatial scale effects on the value of ecosystem services in China's terrestrial area - Changsheng Xiong; Huiyu Ren; Dan Xu; Yueming Gao (Journal of Environmental Management, 2024)

Motion Analysis of International Energy Agency Wind 15 MW Floating Offshore Wind Turbine under Extreme Conditions - Zengliang Chang; Yueming Zheng; Meng Qu; Xingguo Gao; Xiaojie Tian; Guijie Liu (Journal of Marine Science and Engineering, 2024)
In recent years, ultra-large-scale offshore wind turbines have attracted widespread attention. However, accurately evaluating the motion responses of offshore wind turbines under extreme conditions, especially for semisubmersible floating off-shore wind turbines, is often challenging. In order to assess the operational behavior of wind turbines under wind and wave loads, this paper adopted a numerical analysis method to solve the motion responses under extreme conditions. It specifically examines the motion responses of the IEA 15 MW wind turbine in terms of surge, heave, and pitch direction, focusing on environmental loads that occur once every 50 years. The results show that the wind turbine can still operate normally under the Ultimate condition. However, the average amplitude increased by 7% in the pitch direction and decreased by 4% in the heave direction compared to the rated condition. Under extreme conditions (occurring once every 50 years), with the wind turbine parked, the average amplitude in the surge direction reduced by 33%, while the average amplitude in the pitch direction reduced by 106%. Thus, it is essential to pitch the blades and brake the generator in extreme environmental conditions to ensure the safety of the wind turbine.

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Pore shrinkage capacity of Shajiang black soils (Vertisols) on the North China Plain and its influencing factors - Yueming CHEN; Zhongbin ZHANG; Lei GAO; Zichun GUO; Peng XIONG; Fahui JIANG; Xinhua PENG (Pedosphere, 2024)

Evaluation of coastal zone development and utilization considering natural ontology, a case study in Liaoning Province, China - Guo Yu; Zhihua Wang; Yueming Liu; Xiaomei Yang; Junyao Zhang; Ku Gao (Ocean & Coastal Management, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

Changes in the spatial distribution of mariculture in China over the past 20 years - Yueming Liu; Zhihua Wang; Xiaomei Yang; Shaoqiang Wang; Xiaoliang Liu; Bin Liu; Junyao Zhang; Dan Meng; Kaimeng Ding; Ku Gao; Xiaowei Zeng; Yaxin Ding (Journal of Geographical Sciences, 2023)

Multiple metabolomics comparatively investigated the pulp breakdown of four dragon fruit cultivars during postharvest storage - Qixian Wu; Huijun Gao; Ziming You; Zhengke Zhang; Hong Zhu; Mingyang He; Junxian He; Xuewu Duan; Yueming Jiang; Ze Yun (Food Research International, 2023)

Study on structure-activity relationship (SAR) of simplified mirogabalin derivatives as voltage-gated calcium channel α2δ ligands for the treatment of chronic neuropathic pain - Yuanwen Zhang; Yueming Zheng; Qingqing Wu; Fuyun Tian; Chuanjun Ma; Haiyan Xu; Li Zhan; Zhaobing Gao; Guilong Zhao; Huihui Ti (Medicinal Chemistry Research, 2023)

Decreasing Vulnerability of Storm Surge Disasters in Coastal Cities of China over the Past 30 Years - Dan Meng; Yueming Liu; Zhihua Wang; Xiaomei Yang; Xiaoliang Liu; Junyao Zhang; Ku Gao (Journal of Marine Science and Engineering, 2023)
From 2000 to 2020, storm surges occurred 397 times in China, resulting in direct economic losses of up to CNY 220.64 billion. Storm surges not only threaten safety but also cause property damage; hence, it is necessary to assess the changes in vulnerability to storm surges in order to understand how to reduce said vulnerability. Fifteen coastal cities of four types were chosen, with different levels of urban development, rapid expansion of impervious surface, high extent of agricultural land, and high fishery output value. Viewing vulnerability through the dimensions of exposure, sensitivity, and adaptability, a GIS and RS were used to evaluate and assess the vulnerability in 15 coastal cities in China over the past 30 years. The results indicated that the vulnerability of these 15 Chinese cities presented the characteristics of a continuous downward trend from 1990 to 2020, and the average rate of reduction in vulnerability over the 10 years from 2005 to 2015 was the highest, at 2.23%. The areas of high vulnerability shifted from the southern region to the northern region. The vulnerabilities in the southern region, with Shanghai, Shenzhen, and Dongguan, changed significantly, to 3.30%, 3.20%, and 3.45%, respectively. An important factor in determining vulnerability reductions is a city’s ability to adapt to storm surges. Coastal cities can improve their adaptability to storm surge disasters through general public budget expenditure, investment in fixed assets, GDP, and medical and health services, thereby alleviating their vulnerability. Due to China’s frequent storm surge disasters during the 2005–2015 period, government departments have strengthened the investment of relevant resources in adaptive indicators, ultimately causing the cities’ vulnerability to rapidly decrease during this period.

Integration of metabolomics and proteomics analysis to explore the mechanism of neurotoxicity induced by receipt of isoniazid and rifampicin in mice - Xiaoyu Qu; Jie Ma; Huan Gao; Yueming Zhang; Jinghui Zhai; Jiawei Gong; Yanqing Song; Tingting Hu (NeuroToxicology, 2023)

Functional traits and stand factors as strong drivers of radial growth response to hotter drought in a temperate forest of North China - Xuemei Wang; Kai Xu; Wenhao Miao; Linhao Gao; Saif Ullah; Yueming Lyu; Xiangping Wang (European Journal of Forest Research, 2022)

Study on calculation and validation of tropospheric ozone by ozone monitoring instrument – microwave limb sounder over China - Yueming Hu; Huanhuan Yan; Xingying Zhang; Yi Gao; Xiangdong Zheng; Xuyan Liu (International Journal of Remote Sensing, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

Experimental Research on the In Vitro Antitumor Effects of Crataegus sanguinea - Jianling Sun; Guolan Gao; YuLian Gao; liJuan Xiong; Xiaoying Li; Jihong Guo; Yueming Zhang (Cell Biochemistry and Biophysics, 2013)

Phylogenetic relationship of a new class of LMW-GS genes in the M genome of Aegilops comosa - Ke Wang; Liyan Gao; Shunli Wang; Yanzhen Zhang; Xiaohui Li; Miaoyi Zhang; Zhenze Xie; Yueming Yan; Matthew Belgard; Wujun Ma (Theoretical and Applied Genetics, 2011)